Evaluating the Accuracy of Different Local Climate Zone Maps - A. S. Akbulut; E. Sertel (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Local Climate Zones (LCZs) are essential for understanding urban climates, providing crucial information for urban planning, environmental monitoring, and addressing challenges like the urban heat island effect. This study evaluates the accuracy of various LCZ maps, including those from the World Urban Database and Access Portal Tools (WUDAPT), and two independent studies by Demuzere et al. (2022) and Oliveira et al. (2020). Our analysis focuses on five major cities: Istanbul, Athens, Barcelona, Lisbon, and Paris, and explores how geographic, historical, and urban planning factors influence both LCZ classifications and their accuracy. We identify and analyze misclassifications within these maps, investigating the root causes of errors, such as misaligned or insufficient sample data, low spatial resolution of input images and inadequate vector data. Our results reveals that while LCZ maps generally perform well in certain urban settings, their accuracy diminishes in more complex or heterogeneous environments. The findings underscore the importance of refining data quality, classification methods, and spatial resolution to improve the reliability of LCZ maps, offering valuable insights for urban and regional planning, environmental management, and future research on urban climate dynamics.